Importance of risk management in highway and railway constructions - Rozsypal, Alexandr (Univerzita Pardubice, 2010)
The paper focuses on the role and importance of the risk management during construction of highways and railways. For this purpose the engineering riskn will be defined. The main principles of geotechnical risk will be explained. Some cases stories of undesirables events during construction of underground works will be presented and discussed. In the conclusion author will underlines main conditions of succesfull risk management principles to be respected.
Keywords: civil engineering works; failure; geotechnical risk; monitoring; risk; risk manager; risk management; undesirable event